Fluorescent superparamagnetic iron oxide core-shell nanoprobes for multimodal cellular imaging - Smitha, Sasidharan; Haseena, Vadakkenchery S.; Narayanan, Tharangattu N.; Mary, Antony P. Reena; Ajayan, Pulickel M.; Puthumana, Jayesh; Aziz, Anas A.; Aburto, Rebeca R.; Mani, Sendurai A.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Materials Express, 2012)
Multimodal imaging agents that combine magnetic and fluorescent imaging capabilities are desirable for the high spatial and temporal resolution. In the present work, we report the synthesis of multifunctional fluorescent ferrofluids using iron oxide as the magnetic core and rhodamine B as fluorochrome shell. The core-shell structure was designed in such a way that fluorescence quenching due to the inner magnetic core was minimized by an intermediate layer of silica. The intermediate passive layer of silica was realized by a novel method which involves the esterification reaction between the epoxy group of prehydrolysed 3-Glyidoxypropyltrimethoxysilane and the surfactant over iron oxide. The as-synthesized ferrofluids have a high saturation magnetization in the range of 62-65 emu/g and were found to emit light of wavelength 640 nm (lambda(excitation) = 446 nm). Time resolved life time decay analysis showed a bi-exponential decay pattern with an increase in the decay life time in the presence of intermediate silica layer. Cytotoxicity studies confirmed the cell viability of these materials. The in vitro MRI imaging illustrated a high contrast when these multimodal nano probes were employed and the R2 relaxivity of these sample was found to be 334 mM(-1)s(-1) which reveals its high potential as a T2 contrast enhancing agent.
Keywords: GPTMS; MRI Imaging; Multimodal Imaging; SPION; T2 Contrast Agent